Antecedents of employees’ engagement in malaysian private higher education - Seddikin, Nuratikah Shamila Mohd; Burhanuddin, Mohd Nazrin; Osman, Zahir (International Journal of Economics, Business and Management Studies, 2023)
This research study aims to examine the direct relationships between peer influence, leadership style, and organizational culture, and their impact on organizational commitment and employee engagement in private higher education institutions in Malaysia, for both academic and non-academic staff. The significance of this research lies in the fact that many private higher education institutions in Malaysia are experiencing low levels of employee engagement, which can negatively affect organizational performance and productivity. The research model consists of three independent variables (peer influence, leadership style, and organizational culture), with organizational commitment acting as a mediator and employee engagement as the dependent variable. To gather primary data, the study used a survey questionnaire adapted from previous research studies and collected 268 usable responses. The data was then analysed using structural equation modelling to test the hypotheses. The first step in the analysis was to evaluate the measurement model for convergent validity by assessing construct reliability and validity. Then, discriminant validity was assessed and confirmed using cross-loading and Hetrotrait-Monotrait (HTMT) ratios. Finally, the structural model was assessed to test the research hypotheses. The results indicate that peer influence, leadership style, and organizational culture all have a significant positive impact on organizational commitment, which in turn strongly affects employee engagement. These findings suggest that private higher education institutions in Malaysia should focus on improving peer relationships, leadership style, and organizational culture to enhance employee engagement and ultimately improve organizational performance.